Design and Implementation of Vehicle Automatic Emergency Pull over Strategy Using Active Safety Systems on a Driving Simulator - Javaid, Wasif; Deng, Qiwen; Chen, Yaobin; Chien, Stanley (International Journal of Automotive Engineering, 2018)
This paper addresses a critical issue of automotive safety. Advanced Driver Assist Systems (ADAS) are getting enormous reputation with the increasing traffic on roads day by day. This paper presents a design of an Automatic Emergency Pullover (AEP) strategy using active safety systems for a semi-autonomous vehicle on a driving simulator. The idea of this system is that a moving vehicle equipped with an AEP system can automatically pull over on the roadside safety shoulder when the driver is considered incapable of driving. AEP requires supporting features such as Lane Keeping Assist (LKA), Blind Spot Monitoring (BSM), Vehicle and Pedestrian Automatic Emergency Braking (AEB), and Adaptive Cruise Control (ACC) for its execution. The design for application of AEP system has been explained along with its algorithm development and component structure. The implementation of AEP system has been explained along with its vehicle behavior and trajectory precision using software tools provided by Realtime Technologies, Inc. All major variables that influence the performance of vehicle after AEP activation, have been observed and remodeled according to control algorithms. The working of AEP system and its vehicle control strategy has been verified with the help of simulation results.